Empon-Empon Increases Body Immunity During the Climacterium Period - Kusmiyati Kusmiyati; Gusti Ayu Tirtawati (Universitas Aisyah Pringsewu, 2023)
The climacterium period including the elderly is a vulnerable group to the Covid-19 Virus. As a person ages, the body will experience various decreases in body functions due to the aging process which causes the immune system to be weak and more difficult to fight infections. As a result, the body will be more susceptible to diseases, including the Covid-19 virus. There is one way to prevent the transmission of COVID-19, by increasing endurance through the consumption of supplements and herbs such as empon-empon. This type of research is a quasi-experiment using a pre-post test one group design determined using Purposive sampling of 100 respondents with inclusion criteria: Mothers who experience climacterium age range over 40 years, healthy (not suffering from respiratory tract infections and allergies), and they are willing to consume empon-empon 2 times a day (1 sachet) for 30 days. This data is generated through observation sheets and analyzed using paired sample t-test. The paired sample t test results showed that the body immunity before the intervention had an average symptom (mean) of 1.40, the body immunity after the intervention of 15 days of average symptoms (mean) 0.24, after the intervention of 30 days the average (mean) 0.08. There was a decrease in symptoms before the intervention and after the 15-day intervention and after the 30-day intervention and there was a significant difference between the body immunity before and after the intervention, meaning that there was an effect on increasing endurance. From the results of this study, it is expected that people will often consume empon-empon to increase the body immunity.